Optimized design and performance evaluation of a highly precise variable rate mis-planting and replanting potato electronic-metering mechanism - Elwakeel, Abdallah Elshawadfy; Elbeltagi, Ahmed; Salem, Ali; Dewidar, Ahmed Z. (Frontiers in Plant Science, 2025)
IntroductionPrecise seed placement during potato planting critically determines crop distribution and density, yet mis-planting remains a persistent agricultural challenge. Current manual detection and correction methods introduce inefficiencies, increase labor costs, and risk human error.MethodologyTo address these limitations, this study developed and evaluated a high-precision variable-rate electronic metering mechanism (EMM) capable of automated mis-planting detection and replanting under controlled laboratory conditions. The EMM was built to operate at different planting distances and travel speeds, with its design focusing on finding the best mechanical setup before testing it in the field at four different planting distances (24.12, 31.06, 34.87, and 41.24 cm) and five speeds (2.13-6.11 km/h).ResultsThe obtained results demonstrated optimal stability at lower speeds (2.13-3.07 km/h), where sensor accuracy remained consistent, achieving peak performance (QI=98.7%, RI=100%, minimal MPI) at 41.24 cm spacing and 2.13 km/h. Performance degraded significantly at higher speeds (3.94-6.11 km/h), with factorial analysis confirming both speed and spacing as statistically significant factors affecting all indices. Furthermore, the total cost of the developed system was approximately $130 USD.DiscussionFuture experiments will include further field experiments to study the influence of field variables such as soil type, surface irregularity, and environmental disturbances on the performance of the EMM.